Representation of Inner Family Communication Film, Semiotic Analysis John Fiske: Reperesentasi Komunikasi Keluarga dalam Film, Analisis Semiotika John Fiske - Maulana, Dandy; Aesthetika, Nur Maghfirah (Indonesian Journal of Innovation Studies, 2023)
This study aims to determine the representation of family communication in the film "Nanti Kita Cerita Tentang Hari Ini" through John Fiske's semiotic analysis. This research is based on the development of film in Indonesia, which is a form of mass media that has a function to convey information or messages. Effective family communication is essential to maintaining intimate family relationships. Therefore, communication between husband and wife, communication between children and their parents needs to be built effectively in building good harmony in the family. Likewise, the family communication that occurred in the film “Nanti Kita Cerita Tentang Hari Ini”. The researcher uses this type of research using qualitative descriptive, then using John Fiske's semiotic analysis into three levels, namely the level of reality, the level of representation, and the level of ideology. The research results obtained are from 30 scenes there is 1 scene that contains and represents family communication in the NKCTHI film. From the 12 scenes, there are 5 general categories of family communication in this film, namely openness, empathy, support, positive attitude and equality or similarity.